THE USE OF CANVA APPLICATION TO DEVELOPING INTEGRATED LANGUAGE SKILLS TEACHING MATERIALS BASED ON LOCAL WISDOM - Herlina Usman; Nina Nurhasanah; Yulia Elfrida Yanty Siregar (European Journal of Humanities and Educational Advancements, 2023)
In the 21century Teacher had to develop a digital literalation based on local wisdom particularly in creating the learning media. This training makes the learning media use the canva to implementation improve the skills and the digital literalation of the school teacher’s primary of the Karangwitan district of the Kabupaten Garut.This activity runs in three phases, pre-training, training and post-training.The pre-training stage is pre-preparatory stage such as the setting up of events, taking care of the permit, prepare the material and questionnaire. The Implementation Stage or core of this training activity begins with providing a pre-training questionnaire, giving a presentation, as well as training and guidance in making Integrated Language Skills teaching materials based on Cultural Wisdom using media of Canva. The final stage of post-training or evaluation is the provision of post-training questionnaires, assignment/creation of projects by participants, and application of the Canva learning media in the learning process. The results of this training showed that 82% of teachers gave positive perceptions and were interested in using Canva to create digital learning media and 85% of teachers thought that Canva media was easy to use and increased students’ learning motivation. However, 78% of teachers still need assistance regarding making Integrated Language Skills teaching materials based on cultural wisdom to make them more variety. Based on the implementation of the training, it can be concluded that this Canva media creation training has an impact on learning, including teachers being able to know how to make more creative teaching materials or learning media, learning becomes more creative and less monotonous and can motivate students to receive lessons in class.